2016
DOI: 10.1111/1471-0528.14256
|View full text |Cite
|
Sign up to set email alerts
|

Double‐balloon catheter versus prostaglandin E2 for cervical ripening and labour induction: a systematic review and meta‐analysis of randomised controlled trials

Abstract: Double-balloon catheter versus prostaglandin E2 for cervical ripening and labour induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 21 publications
4
38
0
2
Order By: Relevance
“…35 Depending on the study, the likelihood of vaginal delivery within 24 hours varies widely when comparing the balloon to the dinoprostone pessary, with better, worse, or identical effectiveness. 10,12,[36][37][38] We chose to exclude women with previous caesareans from our analysis. Keeping them would have resulted in a major selection bias because some maternity units contraindicate the use of prostaglandins in the event of a scarred uterus and prefer to use the balloon catheter method in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Depending on the study, the likelihood of vaginal delivery within 24 hours varies widely when comparing the balloon to the dinoprostone pessary, with better, worse, or identical effectiveness. 10,12,[36][37][38] We chose to exclude women with previous caesareans from our analysis. Keeping them would have resulted in a major selection bias because some maternity units contraindicate the use of prostaglandins in the event of a scarred uterus and prefer to use the balloon catheter method in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Professionals use it especially in women with previous caesareans or to improve fetal tolerance, because it mechanically ripens the cervix without causing contractions . Depending on the study, the likelihood of vaginal delivery within 24 hours varies widely when comparing the balloon to the dinoprostone pessary, with better, worse, or identical effectiveness . We chose to exclude women with previous caesareans from our analysis.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study examines data drawn from women who were predominantly induced with a chemical induction via prostaglandins. Several authors have demonstrated that balloon catheter IOL is just as efficacious as prostaglandin IOL . One particular study demonstrated an increased rate of unassisted vaginal delivery, reduced post‐partum blood loss and better fetal outcomes with balloon catheter IOL .…”
Section: Discussionmentioning
confidence: 99%
“…Balloon catheters are widely used for cervical ripening. They allow gentle ripening of the cervix, causing less uterine overstimulation [1][2]. However, IAI was one of the most severe complications during induction with balloon catheter.…”
Section: Discussionmentioning
confidence: 99%